Moving Research on International new Ventures Forward: A Systematic Reviews on Case Studies - Leão, Pablo; Santos, Renato Souza (Internext, 2021)
Objective: We delve into the rapid internationalization literature to provide a literature review on the most recent empirical research on international new ventures (INVs). We focus on reporting how the literature on INVs has evolved through the lenses of case studies, and we highlight issues on the use of INVs concepts. Method: We conducted a systematic review of 99 case studies articles related to international new ventures published in leading journals in all areas of knowledge within management. We performed a two-cycle coding and a thematic analysis. Main Results: We have found researchers are applying INV and BG concepts interchangeably, thus incorrectly. Scholars have not considered nor discussed the theoretical implications of dropping and adding criteria when selecting cases. We also found the research in INV has thematically evolved as scholars have increasingly studied the post-internationalization moment of these companies. Relevance/originality: We contribute to the INV’s literature by demonstrating the theory is now evolving to understand the post-internationalization moment of these companies. We also discuss the implication of selecting cases disregarding the criteria that qualify them as INVs. Theoretical/methodological contributions: Our research contributes with a discussion on the implications of loosely applying the INVs concepts and offers insights on how the literature has evolved.